• 2022-06-11
    求函数f1(t)=(1+t)[u(t)-u(t-1)]和f2(t)=u(t-1)-u(t-2)的卷积f1(t)*f2(t)。
  • 用拉普拉斯变换L{f1(t)*f2(t)}=L(u(t))L(e^-at乘u(t))=1/S(S+a)=[1/S-1/(S+a)]/a;求逆变换:f1(t)*f2(t)=1/a(1-e^-at)u(t).

    内容

    • 0

      设f1(t)=2[u(t一7)一u(t一1)],f2(t)=0.5[u(t一5)一u(t一2)]。用图解法求s(t)=f1(t)*f2(t)。

    • 1

      已知f1(t)=u(t+1),f2(t)=u(t+2)-u(t-2),设y(t)= f1(t)* f2(t),则y(0)等于() A: 0 B: 1 C: 2 D: 3

    • 2

      已知f(t)=u(t-1)-u(t-2),且s(t)=f(t)*f(t),则s(3)=? <br/>______

    • 3

      假设f1(t)和f2(t)如图所示,f(t)=f1(t)*f2(t),则f(1)= ( )[img=356x170]18037095681b0cf.png[/img] A: 2 B: -2 C: 4 D: -4

    • 4

      已知f1(t)和f2(t)波形如下,若f(t)=f1(t)*f2(t),则f(0)= A: 1 B: 2 C: 3 D: 4